Development of high‑resolution melting analysis for ABCB1 promoter methylation: Clinical consequences in breast and ovarian carcinoma - Vaclavikova, Radka; Klajic, Jovana; Brynychova, Veronika; Elsnerova, Katerina; Alnaes, Grethe I G; Tost, Jörg; Kristensen, Vessela N; Rob, Lukas; Kodet, Roman; Skapa, Petr; Mrhalova, Marcela; Soucek, Pavel (Oncology reports, 2019)
Multidrug resistance to anticancer drugs, which is often associated with enhanced expression of the ATP‑binding cassette (ABC) transporter P‑glycoprotein (encoded by the ABCB1 gene) may limit the effects of cancer therapy. Epigenetic regulation of ABCB1 expression may thus have a clinical impact. A detailed assessment of ABCB1 promoter methylation is of importance for predicting therapy outcome and prognosis. Thus, validated methods for the analysis of ABCB1 promoter methylation are urgently required. In the present study, high‑resolution melting (HRM) analysis of the CpG island regions covering the distal promoter of the ABCB1 gene was developed and compared with pyrosequencing. In addition, the clinical effects of the methylation status of the ABCB1 promoter were analyzed in patients with breast and ovarian carcinoma prior and subsequent to chemotherapy treatment. HRM analysis of ABCB1 methylation correlated with the results of pyrosequencing (P=0.001) demonstrating its analytical validity and utility. Hypermethylation of the analyzed ABCB1 promoter region was significantly correlated with low levels of the ABCB1 transcript in tumors from a subset of patients with breast and ovarian carcinoma prior to chemotherapy but not following treatment. Finally, high ABCB1 transcript levels were observed in tumors of patients with short progression‑free survival prior to chemotherapy. Our data suggest the existence of functional epigenetic changes in the ABCB1 gene with prognostic value in tumor tissues of patients with breast and ovarian carcinoma. The clinical importance of such changes should be further evaluated.
Keywords: Carcinoma, Ductal, Breast; Neoplasm Invasiveness; Breast Neoplasms; epigeneze genetická; Nucleic Acid Denaturation; Retrospective Studies; Prognosis; regulace genové exprese u nádorů; denaturace nukleových kyselin; serózní cystadenokarcinom; polymerázová řetězová reakce; Epigenesis, Genetic; Polymerase Chain Reaction; Promoter Regions, Genetic; míra přežití; nádory vaječníků; ATP Binding Cassette Transporter, Subfamily B; Follow-Up Studies; Biomarkers, Tumor; následné studie; duktální karcinom prsu; ženské pohlaví; nádorové biomarkery; prognóza; retrospektivní studie; Gene Expression Regulation, Neoplastic; metylace DNA; Humans; Survival Rate; invazivní růst nádoru; DNA Methylation; promotorové oblasti (genetika); nádory prsu; P-glykoproteiny; Cystadenocarcinoma, Serous; Female; Ovarian Neoplasms; lidé